The European Commission as a driver of change: State aid, neoliberalism and the closure of the Amsterdam shipyards - Keulen, Sjoerd; Kroeze, Ronald (TSEG - The Low Countries Journal of Social and Economic History, 2022)
By analysing the case of the closure of the Amsterdam shipyards in the 1980s, this article shows how the European Commission (EC) actively promoted a neoliberal turn in policies on state support for economic sectors in Western Europe. In addition to the EC, leading civil servants within the Dutch ministries of Economic Affairs and Finance emerged clearly as embracing neoliberal ideas early on as an answer to tackle the economic crisis of the 1970s. A third, often neglected factor in explanations for the rise of neoliberalism were management consultants – in this case from management consultancy firm McKinsey – who wrote alarming reports about the shipbuilding industry and promoted ideas that emphasized the importance of business principles and individual managers as key for improvement, thereby offering an alternative to macroeconomic Keynesian models of growth.